Evolving Insights into the Molecular Neuropathology of Diffuse Gliomas in Adults - Barthel, Floris P. (Neurol Clin, 2018)
The field of neuropathology has a long histology-based tradition of glioma classification. Recent advances in molecular analysis and genome sequencing have prompted a paradigm shift in traditional neuropathology. We discuss the discovery and clinical relevance of molecular biomarkers in diffuse gliomas in adult patients and how these biomarkers led to the revision of the 4(th) edition of the World Health Organization (WHO) classification of these tumors. We relate the progress in clinical classification to an overview of studies using molecular profiling to study gene expression and DNA methylation to categorize diffuse gliomas in adults and issues dealing with intratumoral heterogeneity. Together, these efforts can be expected to further refine the taxonomy of diffuse gliomas, to facilitate selection of more appropriate treatment regimens, and to ultimately improve the lives of the patients that suffer from these tumors.